ANALISIS PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. MENARA ABADI PERSADA MEDAN - Simbolon, Dwi Maria (UNIKA Santo Thomas, 2024)
This study explores the impact of leadership style, working environment, and compensation on employee performance at PT. Menara Abadi Persada Medan. Using a descriptive and quantitative approach with 76 employees as respondents, the research employs questionnaires to collect data. Analysis involves validity and reliability tests, descriptive analysis, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, multiple linear correlation coefficient test, t-test for partial hypothesis, F-test for simultaneous hypothesis, and determination coefficient calculation. Results show that leadership style, working environment, and employee performance are very good, while compensation is good. Partial analysis indicates a positive and significant influence of leadership style, working environment, and compensation on employee performance. Simultaneously, these factors collectively contribute 92.5% to enhance employee performance, with 7.5% influenced by unexamined variables like work commitment, discipline, job satisfaction, and others.